(untitled) (Journal of the College of Basic Education, 2022)
This study aimed at identifying the degree of psychologiques alienation among Foreign Students,As well as identifying the differences in the level of psychological alienation according to the variable of educational level,The sample consisted of 73 female students from Western Sahara, scale psychological alienation was applied to them,The data was statistically processed by the statistical package for social sciences (SPSS)program,The results revealed the presence of psychological alienation is low among the students of Western Sahara,And there is no differences in the degree of psychological alienation among Western Saharan students according to the educational level variable.